Clinical and molecular classification of vulvar squamous pre-cancers. Issue 4 (7th May 2019) - Cohen, Paul A; Anderson, Lyndal; Eva, Lois; Scurry, James
Abstract : Vulvar intraepithelial neoplasia (VIN) is a precursor to vulvar squamous cell carcinoma and is defined histopathologically by the presence of atypia. VIN has been classified into two types: usual vulvar intraepithelial neoplasia (uVIN), which is also referred to as a vulvar high-grade squamous intra-epithelial lesion (HSIL), and differentiated VIN (dVIN). The former is associated with chronic infection by sub-types of the human papilloma virus (HPV), whereas dVIN is HPV-independent and frequently associated with lichen sclerosus. The distinction is important because dVIN has a greater risk of, and more rapid transit to, vulvar squamous cell carcinoma. Furthermore, dVIN-associated vulvar cancers have an increased risk of recurrence and higher mortality than those arising from HSIL. Molecular characterization of vulvar squamous cell carcinoma precursors using next-generation sequencing is a relatively novel, but rapidly advancing field. This review appraises recent studies that have investigated the risks of progression to vulvar malignancy associated with HSIL and dVIN, the prognosis of HPV-dependent and HPV-independent vulvar squamous cell carcinomas, and conducted next generation sequencing mutation analyses to elucidate the genomic profiles underlying VIN. These studies suggest that HSIL and dVIN are characterized by different underlying molecular alterations that may have important implications for treatment and follow-up of women diagnosed with vulvar squamous cell cancer.